Giant Ovarian Tumor Presenting as a Huge Abdomino-Pelvic Mass in a Teenage Girl: A Case Report (Journal of Bangladesh College of Physicians and Surgeons, 2021)
Ovarian cysts are common causes of lower abdominal pain and abdominal distention in females. While most of them are benign and rarely grow immensely to achieve a huge size, they may be neoplastic in origin, reaching enormous dimensions with minimum or without raising any symptoms.Here, we present an interesting case of a 19-year-old female,who presented with huge abdominal swelling and pain in whole abdomen from whom a 9.1 kg borderline mucinous ovarian cyst, occupying the whole abdominal cavity was removed.J Bangladesh Coll Phys Surg 2021; 39(2): 137-141